Fungicides used on postharvest bananas - Ferraz, Marcelo Vieira [UNESP]; Ferreira de Almeida, Luis Carlos [UNESP]; Ferraz, Marcos Vieira [UNESP] (Univ Fed Grande Dourados, 2015)
There is little information available on the postharvest behavior of bananas after the application of fungicides in the Registro-SP region. This study aims to evaluate the soluble solids ((0)Brix), pH, and total acidity of the bananas after the application of fungicides. The experimental outline was completely randomized in a 4x2 fungicidal factorial with two concentrations for each fungicide and two degrees of maturity, plus control treatment using only water, repeated in each season. Each experiment had three replications with four tiers of five fruits. For refrigerated bananas, higher values of (0)Brix were observed in fruits treated with Propiconazole and Imidazole. For non-refrigerated bananas, minor (0)Brix values were observed for fruit treated with Azoxystrobin in autumn and lower pH values and higher acidity for bananas that were treated with Azoxystrobin in winter. We conclude that for refrigerated bananas, the products do not interfere with the quality of the fruit, regardless of their concentrations, in spring, summer and autumn, because the values of (0)Brix, pH and acidity did not differ from the control sample. The same was observed for non-refrigerated bananas in summer and winter.
Keywords: disease; ripening; quality